The Analysis of Classroom Interaction in Speaking Activity: A descriptive Study at the First Year of SMPN 3 Kota Serang - Syafrizal, Syafrizal; Evenddy, Sutrisno Sadji; Lisdiana, Siska (JOURNAL OF DEVELOPING ENGLISH AND LANGUAGE TEACHING, 2015)
The objective of this research is to describe the interaction of speaking activity inside the classroom. The researchers used qualitative research, consisted of 41 students of first year, and were selected to be sample of this research. The observation was taken in three sessions to record the interaction inside the classroom. Then, pattern of classroom interaction analyzed into five characteristics proportion. The lowest interaction characteristic proportion was 22% showed by the teacher control profile. In another result, the lowest interaction characteristic proportion spent 24% of studentâs participation. The findings indicated that the interaction of speaking activity inside the classroom was still in teacherâs dominant activity. This study also revealed to realize the importance of the classroom interaction characteristic and to evaluate and develop teachersâ teaching performance. So, the students could make the classroom interaction more effective and the students get experiences in learning new language. The students also will more enjoy taking a part in the teaching-learning of speaking activities to support their environment class the place of teaching-learning process.